Strategy for Strengthening Pancasila Values through Education to Face the Challenges of the Modern Era - Prastisyar Arkaan Kautsar (Aslim: Journal of Education and Islamic Studies, 2026)
This research aims to understand the relevance of Pancasila values ​​in the modern era and the challenges they face in national and state life. In the modern era marked by globalization and digitalization, Pancasila values ​​face challenges such as political polarization and a national identity crisis, although they remain the foundation of Indonesian unity. This research aims to analyze the relevance of Pancasila and its implementation strategies in national and state life through a literature review. The method involved a journal search using the keywords "Pancasila in the modern era," "challenges in implementing Pancasila," and "relevance of Pancasila values" from 2020-2025, resulting in 20 articles that were narrowed down to 10 key ones. The results indicate that Pancasila is relevant through value recontextualization, integration of education, and public policy, but is hampered by polarization and conflicts of interest. The conclusion recommends innovative approaches such as digital transformation to strengthen the ideology.